ANALISIS IMPLEMENTASI PROGRAM PENINGKATAN KEBERDAYAAN MASYARAKAT PEDESAAN DALAM PENANGGULANGAN KEMISKINAN DI KECAMATAN TAPIAN NAULI KABUPATEN TAPANULI TENGAH - German Sitompul (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
This study aims to determine the implementation, barriers, support, and empowerment activities that become the most effective activity in increasing the empowerment program in rural communities at Sub-District of Tapian Nauli,District of Tapanuli Tengah. The method used in this research is descriptive research with a qualitative approach. The subject selection technique uses purposive sampling and snowball sampling, while the data collection techniques used are observation, interviews, and literature study (documentation). The results shows that the implementation of programs in the empowerment of rural communities at Sub-District of Tapian Nauli, District of Tapanuli Tengah hasnot been able to come to the designated goal. The lack of progress of program activities in increased empowerment of rural communities in this area causes the possibility, strengthening, and protection of powerless groups grow very slowly.Some of the internal factors of the local government are that the supporting programs for activities to increase the empowerment of rural communities are very little, among others, the low availability of inputs especially fund resources,human resources, and lack of bias of government policy itself against the activities of development and poverty alleviation programs. While the barriers of the society as the main target are the low quality of human empowerment of the poor and the presence of several cultural communities still lack support for improving the welfare of rural communities.